2019
DOI: 10.4103/ijcm.ijcm_78_19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of occupational burnout among resident doctors working in public sector hospitals in Mumbai

Abstract: Introduction:Burnout syndrome refers to a combination of physical fatigue and emotional exhaustion, which, in turn, affects the working efficiency of a person. In India, factors such as extensive working hours, poor facilities, and physical and emotional abuse of doctors by patients and seniors lead to the high prevalence of occupational burnout among medical practitioners.Materials and Methods:The sample consisted of 300 resident doctors working in public sector hospitals across Mumbai. The “Copenhagen Burnou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Brain Drain Financial reasons, Social and professional ambitions, religious and gender-related issues, family support, and assistance from migrant networks are the key reasons for migration. 10 [ 17 , 31 , 37 , 48 , 68 , 70 , 80 , 85 , 90 , 97 ] It is difficult for India to retain skilled medical personnel due to the movement of Indian HRH to nations with higher incomes, which affects government efforts to make healthcare more accessible throughout the nation. 5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Brain Drain Financial reasons, Social and professional ambitions, religious and gender-related issues, family support, and assistance from migrant networks are the key reasons for migration. 10 [ 17 , 31 , 37 , 48 , 68 , 70 , 80 , 85 , 90 , 97 ] It is difficult for India to retain skilled medical personnel due to the movement of Indian HRH to nations with higher incomes, which affects government efforts to make healthcare more accessible throughout the nation. 5.…”
Section: Resultsmentioning
confidence: 99%
“…Another significant concern identified by a majority of the research is a lack of HRH databases [23,28,49,82,90]. There is a backlog of shortages because actual HR requirements are not assessed as a result of the lack of routinely updated HR planning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Dhusia et al indicated that young resident doctors studying and/or working in public sector hospitals of Mumbai also experienced extremely high levels of burnout mostly due to prolonged hours of duty, on average 88 hours/week 19 . Srivastava et.al found a significant and negative association between job satisfaction and burnout (p=0.01) among Indian doctors who worked in medical colleges, private hospitals, or at their private clinics 20 .…”
Section: Discussionmentioning
confidence: 99%